2008
DOI: 10.4049/jimmunol.181.5.3310
|View full text |Cite
|
Sign up to set email alerts
|

Two Macrophage Colony-Stimulating Factor Genes Exist in Fish That Differ in Gene Organization and Are Differentially Expressed

Abstract: Mammalian macrophage CSF (MCSF; CSF-1) is the primary regulator of the mononuclear phagocyte lineage. We, for the first time, report the complete sequencing of five MCSF cDNAs from three fish species, rainbow trout, zebrafish, and goldfish. Despite the difference in the lengths of the MCSF transcripts, all of the fish MCSF molecules encode a signal peptide, a CSF-1 domain, a transmembrane domain, and an intracellular region. Each fish MCSF gene has a unique exon/intron structure. The primordial MCSF gene may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 53 publications
5
102
0
Order By: Relevance
“…In addition to cells expressing the CD4 molecule, macrophages could also be targeted by CXCL11_L1, CXCL_F4 and CXCL_F5 since elevated transcript levels of MCSFR were seen in the migrated cell fraction. In fish, a putative receptor (CXCR3) for CXCL11_L1 has recently been identified and shown to be expressed in mononuclear phagocytes and macrophages (Aghaallaei et al, 2010;Wang et al, 2008). However, direct interaction between putative fish CXCR3 and CXCL11_L1 has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cells expressing the CD4 molecule, macrophages could also be targeted by CXCL11_L1, CXCL_F4 and CXCL_F5 since elevated transcript levels of MCSFR were seen in the migrated cell fraction. In fish, a putative receptor (CXCR3) for CXCL11_L1 has recently been identified and shown to be expressed in mononuclear phagocytes and macrophages (Aghaallaei et al, 2010;Wang et al, 2008). However, direct interaction between putative fish CXCR3 and CXCL11_L1 has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…RNA preparation, cDNA synthesis, and real-time PCR analysis of gene expression were as described previously (42,43). Six healthy rainbow trout (average weight, 120 g) were killed, and eight tissues (gills, skin, muscle, liver, spleen, HK, intestine, and brain) were collected.…”
Section: Expression Of Til-21 Transcripts In Vivomentioning
confidence: 99%
“…ml), dexamethasone (DM, 0.5 mg/ml), or PHA (from red kidney bean Phaseolus vulgaris; 10 mg/ml) for 4, 8, and 24 h. All the chemicals were from Sigma-Aldrich, and the stimulants were diluted in complete medium just before addition to the cells. The concentrations chosen for each stimulant were deemed optimal from previous studies (43)(44)(45)(46). The treatments were terminated by dissolving the cells in TRIzol (Invitrogen).…”
Section: Preparation Of Hk Cells and Splenocytesmentioning
confidence: 99%
“…Although at this early stage, there is still a considerable infiltration of leukocytes as a result of tissue damage, it might be interesting in the future to study whether CXCL11 L1 is also capable of recruiting B cells as reported in some mammalian species [46], despite the fact that previous evidence in trout suggests that CXCL11 L1 is mainly chemoattractant for macrophages and CD4 + cells [36]. CXCL10 is a gamma interferon inducible CXC chemokine, as is CXCL9 and CXCL11, all of them sharing the same receptor, CXCR3, which in trout has two different isoforms [47]. Interestingly, we have observed a significant up-regulation of CXCR3B in vaccinated animals that suggests that this chemokine-chemokine receptor association is maintained in teleost.…”
Section: Discussionmentioning
confidence: 99%